More than just fields: Reframing deagrarianisation in landscapes and livelihoods. (July 2018) - Hebinck, Paul; Mtati, Nosiseko; Shackleton, Charlie
Abstract: This paper discusses the emergent properties of deagrarianisation processes in two villages in the central Eastern Cape, South Africa. The claim of is that much of the deagrarianisation literature and debate does not acknowledge the importance of landscapes and the interaction between their constituent elements, notably people, forests, grasslands, fields, grazing lands, open spaces, built environments and homesteads, all of which contribute to shaping and, in turn, are shaped by livelihoods. Conceptualising a landscape as a spatial entity and associated assemblage of practices, discourses and history, this paper dissects the landscape in terms of land uses for residential and cultural purposes, growing, grazing and gathering. These land use categories together represent the rural domain to which the villagers are attached as a place and a home. Their use of the land is not necessarily oriented to fully exploring its productive potential. The article explores the transformation from a productive landscape to one which largely hinges on consumption. The blurring of boundaries between the formally designated land use categories signifies the transformations occurring in many of the rural areas in the former homelands of South Africa. Highlights: Deagrarianisation literature has rarely considered landscape transformations. Meanings and interpretations of the land are changing which goes beyond fields only. The rural homestead and lifestyle remains a constant factor in rural dynamics.